The acute effect of foam rolling on strength and flexibility in volleyball players - Ergin, E. (International Journal of Applied Exercise Physiology, 2020)
The present study which aimed to determine the acute effect of foam rolling on strength and flexibility in volleyball players was participated by a total of 21 voluntary volleyball players, 12 males and 9 females ((20.33±1.74 years, 70.09±9.88 kg., 181.47±7.86 cm., 21.13±1.74 kg/m²). The study was designed as a randomized controlled trial and all participants performed 3 different warm-up protocols at 48-72 hour intervals in a randomly appointed order. All participants did 5-minute-jogging exercise before each warm-up protocol and they performed this running activity before all protocols. The 3 different warm-up protocols were designed so as to consist of dynamic warm-up, foam roller and a combination of dynamic warm-up and foam rolleras 3 sets of 30 seconds with 30-second resting time between the sets. The movements were intended for 4 different muscle groups as gluteal, hamstring, quadriceps and calf. Following each protocol, the participants' strength was measured with vertical jumpand countermovement jump performances and sit and reach test was applied to determine their flexibility. For the comparisons of two independent groups, t test was used for those who met the parametric test assumptions and Mann Withney U test for those which did not. For the comparisons of more than two groups in terms of numeric variables, normally distributed groups were tested using OneWayAnova while Kruskal Wallis test was applied for those which did not meet the assumption of normality. The results of the statistical analyses showed that after 3 different warm-up protocols, no statistically significant difference was found between the results of vertical jump, countermovement jump and sit and reach tests (p>0.05). The results of the study revealed thatfoam roller use during warm-up had no acute effect on performance. However, it is considered to possibly affect chronic performance by creating an impact on exercise frequency and volume due to its effects on myofascial release.